2007
DOI: 10.1186/1476-9255-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones avert chronic inflammation-induced bone loss and vascular disease

Abstract: Background: Evidence from epidemiological, clinical and animal studies suggests a link may exist between low bone density and cardiovascular disease, with inflammatory mediators implicated in the pathophysiology of both conditions. This project examined whether supplementation with soy isoflavones (IF), shown to have antiinflammatory properties, could prevent tissue expression of TNF-α and the development of skeletal pathology in an animal model of chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 50 publications
8
47
0
Order By: Relevance
“…We showed that GTP supplementation significantly down-regulated protein expression of TNF-α induced by chronic inflammation. Such a bone-protective effect of GTP supplementation on chronic inflammation agrees with other antioxidant such as soy isoflavones [15,36] using the same model of bone loss. Our current data show that the down-regulation of TNF-α and improvement in bone microarchitecture and quality by GTP supplementation further support the anti-inflammatory role of GTP in bone health which may reduce the risk of bone loss.…”
Section: Discussionsupporting
confidence: 55%
“…We showed that GTP supplementation significantly down-regulated protein expression of TNF-α induced by chronic inflammation. Such a bone-protective effect of GTP supplementation on chronic inflammation agrees with other antioxidant such as soy isoflavones [15,36] using the same model of bone loss. Our current data show that the down-regulation of TNF-α and improvement in bone microarchitecture and quality by GTP supplementation further support the anti-inflammatory role of GTP in bone health which may reduce the risk of bone loss.…”
Section: Discussionsupporting
confidence: 55%
“…It should be noted that a cardiovascular-protective effect of GTP supplementation on chronic inflammation agrees with data on other antioxidants such as soy isoflavones [31] using the same model of myocardial fibrosis. Our current data show that the down-regulation of TNF-a and innate immune responses in cardiovascular pathology by GTP supplementation further support the anti-inflammatory role of GTP in CVD health.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, some mechanisms implicated in the anti-inflammatory effects of flavonoids may contribute to its cardiovascular protection, such as regulation of inflammatory mediators production. In an animal model, Droke et al [184] demonstrated that soy isoflavone administration reduces the risk of cardiovascular disease associated with chronic inflammation, by down-regulating inflammatory mediators such as TNF-a at endothelial level. Furthermore, in vitro studies have revealed that dietary flavonoids such as apigenin, chrysin, kaempferol or quercetin, attenuate the expression of adhesion molecules in human aortic endothelial cells [185].…”
Section: Flavonoids Inflammation and Cancermentioning
confidence: 99%